Kepatuhan Jepang dan Tiongkok terhadap Rezim Internasional Mengenai Penanganan Kejahatan Korupsi dan Pencucian Uang Sebagai Sarana Peningkatan Kekuatan Ekonomi Negara - Purba, Ribka Indriani; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
It is almost undeniable that the existence of interests has basically become the basis of every states in taking policies both domestically and abroad, including Japan and China. In the contemporary era, the scope of state power is no longer limited to the issue of security and defense (military) but also its economic strength. The increasing ofÂ economic power nowÂ has included in the top of the country's interests. In an effort to increase the economic strength of state, Japan and China realize it by overcoming their domestic problems which potentially obstruct the economic growth as well as damage the country's economic stability. The problem in question is the crime of corruption and money laundering and categorized as complex crimes. It takes the role of other actors besides the state who are believed that it is able to help accelerate the handling of these crimes, in this context is the role of the international regime. This argument at the same time also become the main reason of why Japan China comply to the international regime towards corruption and money laundering handling. This research aims to explain that Japan and China comply to the regime is caused by the national interest that the two countries want to achieve, in this case is the interest of increasing the economic strength of Japan and China.